Comparison of Continuous and Discontinuous SVPWM Techniques for Reduced Current Ripple in 2-Phase 3-Leg VSI- Fed Asymmetrical Parameter 2-Phase Induction Motor Drives - Charumit, Chakrapong; Jitson, Tawatchai (Journal of Advanced Development in Engineering and Science, 2023)
This paper presents the comparison of output current ripples for two-phase three-leg voltage source inverter using the continuous and discontinuous space vector pulsewidth Modulation (SVPWM) Techniques fed asymmetrical parameter two-phase induction motor which is modified from capacitor start and run single-phase induction motor. An asymmetrical parameter two-phase motor with a rating of 1Hp, 4 pole, 220 V 50Hz, 5.2A and 1430r/min is used for the test with current ripple to compare with continuous and discontinuous SVPWM technique at the high modulation index. For proposed SVPWM, the current ripple reductions of both stator currents are focused by proposed SVPWM technique divided into 3 techniques as continuous SVPWM techniques (CSVPWM), discontinuous SVPWM type 1 (DSVPWM type 1) and discontinuous SVPWM type 2 (DSVPWM type 2). These DSVPWM techniques are calculated by zero voltage vectors in each sector. DSVPWM type 1 and DSVPWM type 2 are calculated by only one type of zero voltage vector and various types of zero voltage vectors respectively. The experimental results confirm the validity of the proposed techniques. For output current ripple of DSVPWM type 1 and DSVPWM type 2 can be reduced more than the CSVPWM method.